A PRACTICAL GUIDE TO SCIENTIFIC AND TECHNICAL TRANSLATION : Publishing, Style and Terminology - Mitchell, J. B. A., (James Brian Alexander Mitchell); Florescu-Mitchell, Anca Irina (New Jersey : World Scientific, 2022)
"This book is a troubleshooting guide to linguistic and style errors for scientists who are non-native speakers of English, and who need to publish in English journals and apply for patents. Technical terminology searching and choice will be covered with examples from a number of scientific disciplines, with advice on how to choose the right term for the right job. General translation concepts are also discussed, so the book will also be useful to independent technical translators, students of translation, and scientists who need to present their work in languages other than English" -
Includes bibliographical references and index.
Keywords: Science -- Handbooks, manuals, etc. -- Translating; Technology -- Handbooks, manuals, etc. -- Translating; Technical writing -- Handbooks, manuals, etc